2007
DOI: 10.1002/adem.200700154
|View full text |Cite
|
Sign up to set email alerts
|

Development of Investment‐Casting Process of Mg‐Alloys for Aerospace Applications

Abstract: Investment casting offers high‐quality castings with good dimensional accuracy, being therefore suitable for aircraft applications. Since commercial ceramic shells react with Mg melts and appropriate inhibitors being not available, magnesium alloys are not widely used in industrial investment‐casting. In order to overcome this situation and enable the aircraft industry to take advantage of the light‐weight properties of magnesium, the process is analyzed within the European FP6 IDEA project, which aims at deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Many approaches have been of research concern to suppress or control mold-metal reaction such as using vacuum-assisted [4,7], different shell materials [8,9], or controlling the process parameters [10,11], using protective gases and inhibitors [8,12] during investment casting. However, commercially feasible techniques for investment casting of magnesium alloys and producing good surface finish are limited.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Many approaches have been of research concern to suppress or control mold-metal reaction such as using vacuum-assisted [4,7], different shell materials [8,9], or controlling the process parameters [10,11], using protective gases and inhibitors [8,12] during investment casting. However, commercially feasible techniques for investment casting of magnesium alloys and producing good surface finish are limited.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…[1][2][3] Magnesium (Mg) alloys have distinct advantages as structural metallic materials because of their low-density, high-specific strength, good damping capacity, and easy recycling. [1][2][3] Magnesium (Mg) alloys have distinct advantages as structural metallic materials because of their low-density, high-specific strength, good damping capacity, and easy recycling.…”
Section: Introductionmentioning
confidence: 99%
“…The request of weight reduction for structural materials has become increasingly strong in automotive and aerospace industries in recent years. [1][2][3] Magnesium (Mg) alloys have distinct advantages as structural metallic materials because of their low-density, high-specific strength, good damping capacity, and easy recycling. However, the mechanical properties of common Mg alloys such as AZ, AM, and ZK series are relatively poor in high temperatures compared with other metallic materials, which seriously limits their service temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, BF 3 gas released from powder flux KBF 4 additionally removes nonmetallic impurities. [41] Magnesium reacts with almost all ceramic materials that typical shell molds are made of. Alternative slurry materials should be based on less reactive oxides exhibiting possible higher free energy of formation DG and stability.…”
Section: Pattern Castingmentioning
confidence: 99%
“…Unfortunately, this sulfur fluoride is a much worse greenhouse gas than CO 2 , so there is a tendency to replace it or reduce its concentration. Typically, the minimum content is up to 2%, [40] though Arruebarrena et al [41] observed an oxide-free surface of Mg casting when only 9% of SF 6 in CO 2 was used. When the mold cavity is flushed with SF 6 , MgO, and MgF 2 grow on the casting, and due to enhanced capillary force, they spread and join to form a continuous film on the surface of the molten metal.…”
Section: Pattern Castingmentioning
confidence: 99%